Communism, subaltern studies and postcolonial theory : the left in south India - Mannathukkaren, Nissim (Abingdon, Oxon : Routledge, 2022)
This book is a thematic history of the communist movement in Kerala, the first major region (in terms of population) in the world to democratically elect a communist government. It analyzes the nature of the transformation brought about by the communist movement in Kerala, and what its implications could be for other postcolonial societies. The volume engages with the key theoretical concepts in postcolonial theory and Subaltern Studies, and contributes to the debate between Marxism and postcolonial theory, especially its recent articulations. The volume presents a fresh empirical engagement with theoretical critiques of Subaltern Studies and postcolonial theory, in the context of their decades-long scholarship in India. It discusses important thematic moments in Kerala's communist history which include -- the processes by which it established its hegemony, its cultural interventions, the institution of land reforms and workers' rights, and the democratic decentralization project, and, ultimately, communism's incomplete national-popular and its massive failures with regard to the caste question. A significant contribution to scholarship on democracy and modernity in the Global South, this volume will be of great interest to scholars and researchers of politics, specifically political theory, democracy and political participation, political sociology, development studies, postcolonial theory, Subaltern Studies, Global South Studies, and South Asia Studies.
Includes bibliographical references and index.
Nissim Mannathukkaren is Associate Professor in the International Development Studies Department at Dalhousie University, Canada. He is the author of the book The Rupture with Memory: Derrida and the Specters that Haunt Marxism(2006). His research has been published in journals such as Citizenship Studies, Journal of Peasant Studies, Third World Quarterly, Economic and Political Weekly, Journal of Critical Realism, International Journal of the History of Sport, Dialectical Anthropology, Inter-Asia Cultural Studies, and Sikh Formations. He is a regular op-ed contributor to the English-language press in India.
Print version record.
Keywords: Communism -- India -- Kerala -- History; Postcolonialism -- India -- Kerala; Postcolonialisme -- Inde -- Kerala; POLITICAL SCIENCE -- Political Ideologies -- Communism & Socialism; POLITICAL SCIENCE -- History & Theory; Communism; Politics and government; Postcolonialism; Kerala (India) -- Politics and government; India -- Kerala; History